2017
DOI: 10.1007/s11306-017-1311-y
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in lipid, amino acid, and energy metabolism distinguish Crohn’s disease from ulcerative colitis and control subjects by serum metabolomic profiling

Abstract: We demonstrate that a number of lipid-, amino acid-, and tricarboxylic acid (TCA) cycle- related metabolites were significantly altered in IBD patients, more specifically in CD. Therefore, alterations in lipid and amino acid metabolism and energy homeostasis may play a key role in the pathogenesis of CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(131 citation statements)
references
References 49 publications
10
109
0
4
Order By: Relevance
“…Whereas, 286 serum metabolites were found to be significantly changed in CD patients compared with health subjects, only five metabolites were found to be decreased in patients with UC. Fatty acid, acylcarnitine metabolite, sphingolipid, and bile acid metabolism were significantly different in CD patients compared with UC patients and healthy controls (59). Serum metabolite profiles are also different in pediatric CD and UC patients (60).…”
Section: Metabolomicsmentioning
confidence: 94%
“…Whereas, 286 serum metabolites were found to be significantly changed in CD patients compared with health subjects, only five metabolites were found to be decreased in patients with UC. Fatty acid, acylcarnitine metabolite, sphingolipid, and bile acid metabolism were significantly different in CD patients compared with UC patients and healthy controls (59). Serum metabolite profiles are also different in pediatric CD and UC patients (60).…”
Section: Metabolomicsmentioning
confidence: 94%
“…Recent analysis of the lipidome profiles of IBD patients also reflected the role of several pathways that are crucial for epithelial homeostasis, including barrier function and innate immune response [150]. Moreover, Scoville et al showed that the serum metabolomic profile in IBD patients reflected differences in a number of lipid, amino acid, and tricarboxylic acid cycle related metabolites when compared to the healthy controls [151]. In a more recent study, Murgia et al showed that using metabolomics and lipidomics, they were able to differentiate between IBD patients and healthy controls, and more importantly between CD and UC patients [152].…”
Section: Other Omics: Lipidomics and Metabolomics In Ibd Pathogenesismentioning
confidence: 99%
“…Carnitine also has an antioxidant and anti-inflammatory capacity [48,50]. Some studies have reported that acetyl-carnitine and carnitine are associated with liver function, liver diseases, neurologic disorders, and IBD [22,[51][52][53][54]. Therefore, liver damage due to intestinal inflammation occurs as a result of changes in the concentrations of acetyl-carnitine and carnitine.…”
Section: Discussionmentioning
confidence: 99%